TINJAUAN TEORITIS BUDAYA DAN MOTIVASI KERJA TERHADAP SEMANGAT BEKERJA KARYAWAN STEBI LIWA LAMPUNG BARAT - Marliyanti Marliyanti; Mazdayani Mazdayani; Hidayatul Asra (Jurnal AKTUAL, 2020)
This research is based on factors that cannot be ignored related to employee morale, namely work culture and work motivation. This can be reflected in the lack of employee morale because the work culture and work motivation between leaders and staff are still lacking, this can be seen from the discipline of working hours which is still far from what is expected of employees. The purpose of this study was to determine the relationship between work culture and employee morale at STEBI Liwa West Lampung to determine the relationship between work motivation and employee morale and to determine the relationship between work culture and work motivation which are jointly related to employee morale at STEBI Liwa West Lampung. Research result. With regard to work culture, satisfaction, discipline, work results, appreciation are needed, so that employees can quickly complete work, work motivation needs to be increased through education, through promotion, and through mutations, regarding work enthusiasm, it is necessary to increase employee work culture and work motivation employee.